MARGINALISASI PERMAINAN TRADISIONAL BALI DALAM DUNIA ELEKTRONIK: ANTARA IDEALISME DAN PASAR - I Wayan Suardiana (JURNAL IKADBUDI, 2013)
Play, is one of the world's human generation that is growing. Some of the growth of the nation 's important to be good then be given room to play. Because play requires space and time means a representative then becomes important prepare before they start the game.In this era of universality, space and time for our children increasingly limited due to the damage of environment where they play and the strong influence of the modern game. Public space, in the days of regional autonomy is increasingly less attention because each district are competing to increase Natural Revenue District (PAD ) in order to fund the development, so it is not rare that the public arenas constructed notes as one of the play follow exploited. Meanwhile, time to play collectively more narrow in the middle of modern games mushrooming of imports that can be done individually by the children of the archipelago.Provide space for our children to play forward important to note, especially entering into the realm of traditional games such as modern technology, for example. By entering the realm of traditional games to modern, the latter has familiarly by our children then the opportunity to know the game was more open. Keywords: Traditional games, marginalization, and the electronic world.